Financial development, industrial structure and natural resource utilization efficiency in China. (June 2020) - Xu, Li; Tan, Junlan
Abstract: Using 2006–2018 provincial panel data, the robust generalized least squares method and spatial measurement methods are used to conduct an empirical analysis of the relationship between financial development, industrial structure, and natural resource utilization efficiency. It is found that the industrial structure has a negative impact on the utilization efficiency of natural resources, but its significance level and elasticity coefficient are low. This is due to the fact that although China's industrial structure is improved compared with the past, it is still dominated by heavy industries, which has a negative impact on the utilization efficiency of natural resources. Financial development has a positive impact on natural resource use efficiency. Capital can be used to invest limited resources into areas with higher productivity and output growth rates through financial intermediation and financial market reallocation, which will drive the optimization and upgrading of traditional industries. In the context of the control variables, we found that the government investment behavior hindered the improvement of resource utilization efficiency; foreign direct investment significantly improved the efficiency of natural resource utilization. Urbanization variables did not pass the significance level test, and the coefficient value is relatively small, indicating that the development of China's urbanization at this stage cannot significantly improve the efficiency of natural resource utilization. The R&D investment is positively related to the efficiency of natural resource utilization. Finally, the paper proposes countermeasures and suggestions based on the empirical results to improve the efficiency of natural resource utilization for sustainable development. Highlights: The robust generalized least squares method and spatial measurement methods are used. We explored financial development, industrial structure, and natural resource utilization efficiency. Financial development has a positive impact on natural resource use efficiency.